2009
DOI: 10.1007/s11064-009-0015-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of Selenium on Calcium Signaling and Oxidative Stress-induced Molecular Pathways in Epilepsy

Abstract: Epilepsy is one of the oldest neurological conditions known to humankind. It is known that oxidative stress and generation of reactive oxygen species are a cause and consequence of epileptic seizures. Although recent years have seen tremendous progress in the molecular biology and metabolism of selenium, we still know little about the cell type-specific and temporal pattern of selenium and its derivatives in the brain of epileptic humans and experimental animals. It has been suggested that some antiepileptic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
134
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 229 publications
(142 citation statements)
references
References 86 publications
4
134
1
2
Order By: Relevance
“…It has been postulated that low level of zinc in diabetic patients may be due to excessive urinary output and gastro intestinal malabsorption [39,40]. The results of this investigation showed also that there was a significant decrease of zinc content in the previous organs of diabetic animals fed inadequate zinc diet compared to their diabetic fed adequate zinc diet, which was coincide with previous investigations [37,41]. On the other hand zinc concentration in various tissues of zinc deficient diabetic rats treated with methanol extract was restored.…”
Section: Discussionsupporting
confidence: 89%
“…It has been postulated that low level of zinc in diabetic patients may be due to excessive urinary output and gastro intestinal malabsorption [39,40]. The results of this investigation showed also that there was a significant decrease of zinc content in the previous organs of diabetic animals fed inadequate zinc diet compared to their diabetic fed adequate zinc diet, which was coincide with previous investigations [37,41]. On the other hand zinc concentration in various tissues of zinc deficient diabetic rats treated with methanol extract was restored.…”
Section: Discussionsupporting
confidence: 89%
“…15 If the free [Ca 2 þ ] i increases due to the degeneration of cation channel activity, physiologic cell functions will be lost. 16,17 Excessive Ca 2 þ load to the cytosol may induce apoptosis by stimulating the release of apoptosis-promoting factors.…”
Section: Introductionmentioning
confidence: 99%
“…2 It has been reported that, Se and GSHPx participate in epilepsy pathogenesis. 3 The immuno-enhancing 4,5 , anti-viral [6][7][8] , cancer prevention 9-13 effects of Se, the protective role of Se against radiation, 14,15 cardiovascular diseases, 16,17 and reproductive disorders 18,19 have also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…2,20,21 One of the most economical means of supplementing selenium is selenium enriched yeast After growing in Se-containing media, yeast (Saccharomyces cerevisiae, S. cerevisiae) can be harvested with a reproducibly high organic Se content. With currently available strains of S. 3 cerevisiae, up to 3000 ppm of Se level were obtained. 22 Selenium enriched yeast is stable during storage, while inorganic Se could be reduced especially under humid condition, and Se-Met could be oxidized.…”
Section: Introductionmentioning
confidence: 99%